2001
DOI: 10.2458/azu_jrm_v54i1_kretzer
|View full text |Cite
|
Sign up to set email alerts
|

Prairie dog effects on harvester ant species diversity and density

Abstract: The purpose of this study was to determine if black-tailed prairie dogs (Cynomys ludovicianus Ord) influence harvester ant nest density and species composition within the shortgrass prairie biome of southwestern Kansas. Two treatments were established: areas colonized by prairie dogs and areas not colonized by prairie dogs. We recorded 183 harvester ant nests of 3 species. Harvester ant nest density did not differ significantly between prairie dog colonies (3.08 nests ha -1 ) and non-colonized shortgrass prair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Following an intensive poisoning campaign lasting over a century (Merriam 1902), populations of the black‐tailed prairie dog ( Cynomys ludovicianus ) declined by an estimated 98% with prairie dogs now viewed as keystone species (Kotliar 2000) impacting significantly on local biodiversity. Sites colonized by prairie dogs had different ant (Kretzer & Cully 2001) and grasshopper (Russell & Detling 2003) species assemblages to non‐colonized sites. The creation of nutrient‐rich prairie dog ‘towns’ led to the establishment of diverse, nutritious forage (Whicker & Detling 1988; Winter et al .…”
Section: Discussionmentioning
confidence: 99%
“…Following an intensive poisoning campaign lasting over a century (Merriam 1902), populations of the black‐tailed prairie dog ( Cynomys ludovicianus ) declined by an estimated 98% with prairie dogs now viewed as keystone species (Kotliar 2000) impacting significantly on local biodiversity. Sites colonized by prairie dogs had different ant (Kretzer & Cully 2001) and grasshopper (Russell & Detling 2003) species assemblages to non‐colonized sites. The creation of nutrient‐rich prairie dog ‘towns’ led to the establishment of diverse, nutritious forage (Whicker & Detling 1988; Winter et al .…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the individual effects of these rodents on arthropods, and nothing is known about their potential interactive effects on arthropod communities. Studies of prairie dog and kangaroo rat impacts on arthropods have been limited both in geographic coverage and the taxa involved (Wilcomb 1954, O'Meilia et al 1982, Davidson et al 1984, Hawkins and Nicoletto 1992, Valone et al 1994, Schooley et al 2000, Kretzer and Cully 2001, Russell and Detling 2003, Bangert and Slobodchikoff 2006). Given that arthropods represent diverse trophic groups, play important roles in ecosystem processes, and comprise much of the biodiversity in grassland ecosystems (Crawford 1981, Whitford et al 1995), it is important to understand the key drivers that organize the structure of these communities.…”
mentioning
confidence: 99%
“…As voracious predators, camel spiders may drastically influence an arthropod community associated with the vegetation-structure differences between colonies and grassland. Other studies have reported lower abundances of grasshoppers and harvester ants on prairie dog colonies (O'Meilia et al 1982, Kretzer andCully 2001). More-recent research has demon strated higher abundances of grasshoppers and general increases in arthropod diversity on colonies (Russell andDetling 2003, Bangert andSlobodchikoff 2006).…”
Section: ]mentioning
confidence: 95%